Circulating leptin and NF‐κB activation in peripheral blood mononuclear cells across the menstrual cycle. (20th April 2016) - Faustmann, Gernot; Tiran, Beate; Maimari, Theopisti; Kieslinger, Petra; Obermayer‐Pietsch, Barbara; Gruber, Hans‐Jürgen; Roob, Johannes M.; Winklhofer‐Roob, Brigitte M.
Abstract: Using the menstrual cycle as a model, this study focused on longitudinal changes and associations within a physiological network known to play a role in female fertility, including, as biologically active nodes, NF‐κB, leptin and adiponectin, β‐carotene, adipose tissue, and progesterone. In 28 women, leptin, adiponectin, β‐carotene, and progesterone concentrations, NF‐κB p65 and p50 activation in peripheral blood mononuclear cells (known to possess estrogen, progesterone and leptin receptors), total body fat (TBF) and subcutaneous adipose tissue (SAT) mass were determined at early (T1) and late follicular (T2) and mid (T3) and late (T4) luteal phase. Leptin and adiponectin concentrations were higher, while NF‐κB p65 activation was lower at T3 compared with T1. NF‐κB p65 activation was inversely related to leptin concentrations at T1, T3, and T4. β‐Carotene was inversely related to leptin (T1, T2, T4) and SAT (T1, T3, T4). NF‐κB p50 activation was inversely related to TBF (T4) and SAT (T3, T4), and leptin was positively related to TBF and SAT (T1‐T4). Progesterone was inversely related to leptin (T2, T3), adiponectin (T3), TBF (T3, T4), and SAT (T2, T3, T4). By providing evidence of luteal phase‐specific reduced NF‐κB p65 activation in women under physiological conditions, this study bridges the gap between existing evidence of a Th1‐Th2 immune response shift induced by reduced NF‐κB p65 activation and a Th1‐Th2 shift previously observed at luteal phase. For the first time, inverse regressions suggest inhibitory effects of leptin on NF‐κB p65 activation at luteal phase, along with inhibitory effects of leptin as well as adiponectin on progesterone production in corpus luteum. © 2016 The Authors BioFactors published by Wiley Periodicals, Inc. on behalf of International Union of Biochemistry and Molecular Biology. 24(4):376–387, 2016